2003
DOI: 10.1194/jlr.m200136-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic lipid/polymer colorimetric membranes

Abstract: Elucidation of the structure and organization of biological membranes is essential for the understanding of various cellular functions that rely on biochemical processes occurring within membranes, such as response to environmental conditions, signaling mechanisms, cell-cell communication, cell motility, or protein transport. Parameters affecting membrane properties include the molecular composition of the membrane, the structure and fluidity of the lipid bilayer, and the interactions of membrane components wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 24 publications
0
52
0
Order By: Relevance
“…Nevertheless, incorporation of cardiolipin into the 30% electronegative lipid bilayer promoted deeper insertion of Crp4 into the membrane and induced liposomal leakage. Such effect could be attributed to the ability of cardiolipin to increase fluidity of lipid bilayers in model membranes (35) and in bacteria (36). In addition, cardiolipin reportedly forms CL-containing lipid domains in E. coli cells (37), leading us to speculate that CL domains may serve as highly charged “gates” to facilitate Crp4 movement into and through lipid membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, incorporation of cardiolipin into the 30% electronegative lipid bilayer promoted deeper insertion of Crp4 into the membrane and induced liposomal leakage. Such effect could be attributed to the ability of cardiolipin to increase fluidity of lipid bilayers in model membranes (35) and in bacteria (36). In addition, cardiolipin reportedly forms CL-containing lipid domains in E. coli cells (37), leading us to speculate that CL domains may serve as highly charged “gates” to facilitate Crp4 movement into and through lipid membranes.…”
Section: Discussionmentioning
confidence: 99%
“…For diverse membrane processes, colorimetric assay can be adopted for studying enzymatic cleavage of lipids, 1 screening of antimicrobial peptides, 2 membrane-peptide interaction, 3 ion sensing, 4 and assessing membrane penetration enhancers. 6 Recently, many studies have reported about the sensor fabrication using 10,12-pentacosadiynoic acid (PCDA) and its derivatives. 6 Recently, many studies have reported about the sensor fabrication using 10,12-pentacosadiynoic acid (PCDA) and its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…An important question this study aims to address concerns the dependence of membrane interactions of VV upon bilayer makeup and organization. In that regard, the lipid composition of the chromatic lipid/PDA vesicle platform can be easily varied (25). Figures 2 to 5 present experimental results designed to evaluate the extent of bilayer binding, penetration, and membrane fusion of vaccinia virus and examine the relationship between these parameters and lipid constituents in the bilayer.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 depicts the principle of the lipid/PDA vesicle assay for studying membrane interactions. The mixed vesicles comprise both lipid domains, constituting the biomimetic membrane platform interspersed within the PDA matrix that functions as the chromatic reporter for the biological events occurring within the membrane (25). Interactions of viral particles with the lipid/PDA vesicles induce chromatic transformations within the polymer matrix, and analysis of those transformations yield biophysical information on events occurring within the membrane bilayers.…”
mentioning
confidence: 99%